A pulmonary nodule mislocated in “dorsal” segment due to tri-lobed left lung - Lyu, Xiaohong; Xu, Yuan; Qin, Yingzhi; Ma, Dongjie; Liu, Hongsheng (Frontiers in Surgery, 2023)
Background: The left lung has two lobes and one fissure, while the right lung has three lobes and two fissures. Accessory fissures can be unexpectedly found in imaging examination and autopsy. However, an actual accessory lobe is rare. Case presentation: During a lung nodule resection surgery, a 68-year-old male patient was found with three lobes and two fissures in his left lung. In addition, the lung nodule was misdiagnosed as located in the lower lobe because the accessory fissure was mis-regarded as the oblique fissure. In the surgery, the lung nodule was found in the upper lobe. This anatomical variation changed the surgical plan. The pathology of the lung nodule was the granulomatous inflammation with caseous necrosis, with the positive antacid stain. The patient was eventually diagnosed with tuberculosis. Literature review: Literature involving the lung accessory fissure and lung accessory lobe variants were reviewed. In ten autopsy and dissection studies, the incidence of accessory fissure in left lung was 13.5% (79/587, ranging from 2.7% to 50.0%), and in right lung was 7.3% (42/575, ranging from 3.1% to 30.4%). The incidence of accessory lobe in left lung was 2.0% (11/547, ranging from 0.0% to 7.4%), and in right lung was 2.6% (14/539, ranging from 0.0% to 17.4%). The incidence of accessory fissure in bilateral lungs identified by chest X-ray or computed tomography ranged from 7.3% to 32.0%. Three surgical case reports inferred accessory lobes, including left upper lobectomy, left lung transplantation, and an open thoracotomy. Conclusion: It is the first clinical case report that showed lung accessory lobe caused the mislocation of a lung nodule. Radiologists and surgeons should be aware of accessory lobe possibility.